Pigmented villonodular synovitis (PVNS) mimicking septic artritis of the knee in a paediatric patient: A case report - Faris Indra Prahasta, Didi Indra; Mohd Anuar Ramdhan, Ibrahim; Elsonmond Vick, Duin; Dayangku Norlida, Awang Ojep (MOA, 2021)
Pigmented villonodular synovitis (PVNS) is a benign but rare proliferative disorder of the synovium. It commonly occurs in adult population and usually presents as monoarticular disease. There are 2 types of PVNS namely localized and diffuse type. This disease often misdiagnosed due to its rarity especially in paediatric patients. Knee involvement is the commonest in paediatric PVNS although other joints such as hip, foot, ankle, hip, sacroiliac joint and multiple joint involvements have also been reported. Paediatric PVNS often misdiagnosed as septic arthritis, juvenile rheumatoid arthritis and bone sarcoma, and the diagnosis is often made late due to its vague presentation. Majority of PVNS cases managed by surgery either via open or arthroscopic synovectomy with exception in a few paediatric patients as described in literatures. This is a case of a knee PVNS in an 11-year-old boy who was initially treated as septic arthritis. The synovium appearance mimics features in PVNS during knee arthrotomy washout and histopathological examination confirmed the diagnosis. The knee symptoms were significantly improved without additional surgery and good functional knee motion after 2 years follow-up with no sign of recurrence.